The Role of Cultural Intelligence in Enhancing Contextual Performance: An Analytical Study of Faculty Members at Al-Kut University College - Mahdi Taban Al-Jaafari , Nada; Salem Mohammed Al-Janabi , Yazan; Jassim Mohammed Al-Asadi, Abdul Hussein (Iraqi Journal for Administrative Sciences, 2026)
The study aims to demonstrate the role of cultural intelligence with its dimensions (cognitive, metacognitive, motivational, and behavioral) as an independent variable in enhancing contextual performance with its dimensions (interpersonal facilitation and job dedication) among the faculty members of Al-Kut University College. The study originated from a research problem that included questions about the nature of the relationship between cultural intelligence at its different levels and contextual performance, and the extent to which its dimensions contribute to explaining this relationship. The study sample consisted of (267) faculty members selected from a population of (993). A questionnaire was used as the main tool for data collection, and the data were analyzed using confirmatory factor analysis, Pearson correlation coefficient, and structural equation modeling (SEM) through SPSS and AMOS programs. The results revealed that cultural intelligence has a positive and significant effect on contextual performance, and that the metacognitive and motivational dimensions had the greatest impact. The study recommended building a university culture that encourages the development of cultural intelligence among faculty members.